Impact Ejecta and Gardening in the Lunar Polar Regions. Issue 1 (25th January 2019) - Szalay, J. R.; Pokorný, P.; Sternovsky, Z.; Kupihar, Z.; Poppe, A. R.; Horányi, M.
Abstract: The Moon is continually bombarded by interplanetary meteoroids. While many of the meteoroid sources are near the ecliptic plane, a significant population of high‐inclination meteoroids exists at 1 au that bombards the lunar polar regions. Building on previous measurements of the response of the lunar impact ejecta cloud to known meteoroid sources, we develop an ejecta model for the entire lunar surface by incorporating the high‐inclination sources. We find that the polar regions of the Moon experience similar quantities of impact ejecta production as the equator. Due to the enhanced impactor fluxes near the equator and at high latitudes on the dawn side, lunar regolith is preferentially distributed to the mid to high‐latitude regions over long timescales, providing a pathway to mix regolith from different regions. We find impact ejecta yields at the Moon to be significantly lower than the Galilean moons, suggesting meteoroids deliver more energy to the local regolith and can be an important driver in the evolution of volatiles near the lunar surface. Additionally, we find that a polar orbiting spacecraft equipped with a dust analyzer can measure appreciable quantities of lunar ejecta near the poles to constrain the water content in the polar regions. Plain Language Summary: The Moon is continually impacted by small particles shed primary from comets, which impact the Moon from a variety of organized directions. These impacts kick up a significant amount of the lunar soil above the lunar surface and sustain a permanently present cloud of ejecta around the Moon. Previous work categorized the ejecta cloud in the Moon's equatorial plane. Here we extend that work to understand the ejecta environment in the high‐latitude polar regions of the Moon. We find that there are significant quantities of impact ejecta generated in the polar regions. Over long periods of time, lunar material is preferentially distributed to the mid to high‐latitude regions, providing a pathway to mix equatorial and polar regolith. Additionally, we find that a polar orbiting spacecraft equipped with a dust analyzer can measure appreciable quantities of lunar ejecta near the poles to constrain the water content in the polar regions. Key Points: Meteoroid bombardment provides a pathway to redistribute lunar regolith Meteoroid impacts into the lunar regolith may deposit more heat into the surface than impacts into hard, icy surfaces A polar orbiting dust detector would sample significant quantities of polar ejecta and potentially characterize lunar surface water content